1987
DOI: 10.1007/bf00048659
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating recovery of the mercury-contaminated Wabigoon/English River system

Abstract: Mercury levels (essentially methyl mercury -MeHg) in sportfish in a 250 km section of the WabigoonEnglish River system remain seriously elevated as a result if the discharge of approximately 10 tonnes of inorganic Hg from a chlor-alkali plant at Dryden, Ontario, Canada which occurred primarily between 1962 and 1970. The discharges resulted in elevated mercury concentrations in water, sediments and biota. For example, Hg in adult Northern Pike inClay Lake routinely exceeded 3/~g/g (ppm). Field studies in 1978-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Other loss mechanisms included partitioning to particles and sediments and, to a lesser extent, to periphyton. Spike Hg partitioned to main environmental compartments within days to weeks, which is also in agreement with previous studies ( , ).…”
Section: Discussionsupporting
confidence: 93%
“…Other loss mechanisms included partitioning to particles and sediments and, to a lesser extent, to periphyton. Spike Hg partitioned to main environmental compartments within days to weeks, which is also in agreement with previous studies ( , ).…”
Section: Discussionsupporting
confidence: 93%
“…In aquatic ecosystems, pH values between 4.7 and 6.0 have favorable physic-chemical characteristics to the Hg methylate. It increases the Hg diffusion of the sediment in the water column and from this to the biota, where it finishes by accumulating high concentration in the organisms on top of the food chain, such as the fish (Phillips et al 1987;Rada et al 1993;Akagi et al 1979;Parks and Hamilton 1987). In the present study, the water pH at the sampling sites was practically constant as it slightly revealed acid to neutral, which coincided with the one obtained from the studies made by Oberdá in 1996(Oberdá 1996.…”
Section: Resultssupporting
confidence: 93%
“…Mercury concentrations exhibited high variability in the crayfish Orconectes virilis across three New England states, and half of the sites (14 of 28 or 50%) had representative animals with mercury levels at or above expected background concentrations ( £ 0.1 lg/g; Parks and Hamilton, 1987). This background concentration represents mercury levels detected in crayfish from isolated water bodies located in pristine habitats of Canada with geology and vegetation similar to our study areas.…”
Section: Discussionmentioning
confidence: 49%
“…Methylmercury halflives within abdominal muscle are very long, leading to bioaccumulation within individuals, and MeHg may account for >75% of the total mercury found in crayfish (Headon et al, 1996). In northeastern North America, background mercury concentrations in crayfish tail muscle are expected to be £ 0.1 lg/g based on surveys of natural lakes in remote Canadian locations removed from any potential point-source contamination (Parks and Hamilton, 1987).…”
Section: Introductionmentioning
confidence: 99%